Optimising recovery in aphasia: Learning following exposure to a single dose of computer-based script training. - Cherney, Leora R.; Braun, Emily J.; Lee, Jaime B.; Kocherginsky, Masha; Van Vuuren, Sarel (International Journal of Speech-Language Pathology, 2019)
Purpose: Intensity of therapy influences outcomes in aphasia treatment, but little is known about optimum dosage across treatment approaches. Improved understanding of the effects of dose could help facilitate clinical decisions that maximise patient outcomes. This study examines learning in individuals with aphasia following exposure to one 60-min dose of computer-delivered script training, with or without a rest break. Method: Twenty participants (6F, 14M; 17 nonfluent, 3 fluent) with chronic aphasia due to left-hemisphere stroke participated. Participants had a mean (SD) age of 56.9 (8.4) years, a mean time post onset of 55.1 (range: 6.4–396.4) months, and a mean (SD) Comprehensive Aphasia Test score of 47.8 (4.0). Participants were exposed to 60 min of training, with or without a rest break, of a three-turn conversational script about either weather or traffic. Treatment was delivered via computer using a virtual clinician that visually modelled speech and guided treatment, promoting treatment fidelity. Oral reading probes for script sentences were administered at baseline (3 times), mid-treatment, immediately post-treatment, and, at various times, up to 2 weeks post-treatment to track script acquisition and maintenance. The study also examined generalisation from a trained script to a conversation with a clinician via a generalisation probe at three time points: baseline, immediately post-treatment, and 2 weeks post-treatment. Result: Following exposure to one dose of script training, participants demonstrated statistically significant improvements in oral reading accuracy and rate of script production on trained probes from baseline to immediately post-treatment and 2 weeks post-treatment. Participants also demonstrated significant change from baseline in generalisation to a conversation with a clinician immediately post-treatment and at 2 weeks post-treatment. Conclusion: Exposure to a single dose of computer-delivered script training may facilitate learning. These results have implications for future research investigating optimal dosage and scheduling parameters.